Dexmedetomidine Attenuates Neurotoxicity in Developing Rats Induced by Sevoflurane through Upregulating BDNF-TrkB-CREB and Downregulating ProBDNF-P75NRT-RhoA Signaling Pathway. (20th June 2020) - Dong, Yunxia; Hong, Wei; Tang, Zhiyin; Gao, Yan; Wu, Xiuying; Liu, Hongtao
Abstract : To investigate the mechanism dexmedetomidine in relieving the neurotoxicity of a developing brain induced by sevoflurane. Sprague-Dawley rats, 6 days old, were randomly divided into three groups. Rats in the control group were inhaled with air after injection of normal saline; rats in the sevoflurane group were injected with normal saline and inhaled with 3% sevoflurane for 2 h in three consecutive day; rats in the dexmedetomidine group were inhaled with 3% sevoflurane after intraperitoneal injection of dexmedetomidine 25 μ g/kg. WB results showed that mBDNF, pTrkB/TrkB, and CREB were significantly decreased in the hippocampus of the sevoflurane group, which are significantly upregulated in the dexmedetomidine group. In the sevoflurane group, proBDNF, P75NRT, and RhoA were significantly increased, which were significantly lower than those in the dexmedetomidine group than those in the sevoflurane group. The expression BDNF was downregulated in the sevoflurane group, while the proBDNF was upregulated in the sevoflurane group. In the Morris water maze test, the escape latency of the sevoflurane group was significantly prolonged. In sevoflurane groups, the number of crossing platform was significantly reduced, the synaptic protein decreased significantly, and this effect was reversed in rats of the dexmedetomidine group. Dexmedetomidine could reduce synaptic plasticity decline in developing rats induced by sevoflurane, through downregulating the proBDNF-p75NTR-RhoA pathway and upregulating BDNF-TrkB-CREB.